Enhanced Neuroprotective Effects of Coadministration of Tetrandrine with Glutathione in Preclinical Model of Parkinson’s Disease - Xiang-Yun Li; Guang-Hai Mei; Qiang Dong; Yu Zhang; Zhuang-Li Guo; Jing-Jing Su; Yu-Ping Tang; Xue-Hong Jin; Hou-Guang Zhou; Yan-Yan Huang (Parkinson's Disease)
Aim. In this study we examined the influence of tetrandrine (Tet) on the neuroprotective effects of glutathione (GSH) in the 6-hydroxydopamine- (6-OHDA-) lesioned rat model of Parkinson’s disease (PD). Methods. Levels in the redox system, dopamine (DA) metabolism, dopaminergic neuronal survival, and apoptosis of the substantia nigra (SN) and striatum, as well as the rotational behavior of animals were examined after a 50-day administration of GSH + Tet (or GSH) and/or L-3,4-dihydroxyphenylalanine (L-dopa) to PD rats. Ethics Committee of Huashan Hospital, Fudan University approved the protocol (number SYXK2009-0082). Results. Administration of GSH or Tet alone did not show any significant effects on the factors evaluated in the PD rats. However, in the GSH + Tet group, we observed markedly decreased oxidative damage, inhibition of DA metabolism and enhanced DA synthesis, increased tyrosine hydroxylase- (TH-) immunopositive neuronal survival, and delayed apoptosis of dopaminergic neurons in the SN. Animal rotational behavior was improved in the GSH + Tet group. Additionally, coadministration of GSH + Tet appeared to offset the possible oxidative neurotoxicity induced by L-dopa. Conclusion. In this study, we demonstrated that tetrandrine allowed occurrence of the neuroprotective effect of glutathione probably due to inhibition of P-glycoprotein on 6-hydroxydopamine-lesioned rat models of Parkinson’s disease, including rats undergoing long-term L-dopa treatment.